Augmenting the bench - Moujan, Carola (Interstices: Journal of Architecture and Related Arts, 2015)
The concept of augmented space opens up new horizons in street furniture design, bringing to life a new, screen-enabled generation of “smart” urban objects. Their deployment, however, is not without issues – from sidewalk cluttering to identity dilution. Beyond technological obsession and nostalgic rejection, I discuss digital placemaking from the perspective of relationships. Starting from Heidegger's distinction between things and objects, and through the case of Luciole, a network of augmented public benches, the article proposes a vision of digital augmentation that, instead of focusing on information, storytelling or function, aims at triggering urban events.